Systemic Treatment of Immune-Mediated Keratoconjunctivitis Sicca with Allogeneic Stem Cells Improves the Schirmer Tear Test Score in a Canine Spontaneous Model of Disease - Hermida Prieto, Manuel; García Castro, Javier; Mariñas Pardo, Luis (My University, 2022)
: Keratoconjunctivitis sicca (KCS) is characterized by ocular discomfort, conjunctival hyperaemia, and corneal scarring, causing reduced aqueous tear production that can be measured using the standard Schirmer tear test (STT). Canine adipose tissue-derived MSCs (cATMSCs) have been proposed as treatment due to their anti-inflammatory effect, by releasing cytokines and immunomodulatory soluble factors. Purpose: The aim of this study was to evaluate the effect of the systemic administration of cATMSCs on tear production in dogs with immune-mediated KCS, compared to classical Cyclosporine A (CsA) treatment. Methods: Twenty-eight client-owned dogs with spontaneous KCS were allocated in the experimental group (n = 14, treated with systemic cATMSCs or control group (n = 14, treated with CsA). SST values increased significantly at days 15 (p = 0.002), 45 (p = 0.042) and 180 (p = 0.005) with no observed side-effects in the experimental group. Eyes with an initial STT value of 11¿14 mm/min maintained significant improvement at day 180, needing only artificial tears as treatment. Eyes with an initial STT value <11 mm/min needed cyclosporin treatment at day 45, so follow-up was stopped. Control animals treated with CsA did not improve their STT at day 180. Results and Conclusions: Systemic allogeneic cATMSCs application appeared to be a feasible and effective therapy with positive outcome in dogs with initial STT between 11¿14 mm/min, with a significant improvement in tear production. The STT increment was maintained for at least 180 days, without needing additional medication, thus suggesting it could constitute an alternative therapy to classical immunosuppressive treatments. Keywords: keratoconjunctivitis sicca; mesenchymal stem cells; Schirmer tear test